Complex Immune Dysregulation in COVID-19 Patients with Severe Respiratory Failure - Giamarellos-Bourboulis, Evangelos J.; Netea, Mihai G.; Rovina, Nikoletta; Akinosoglou, Karolina; Antoniadou, Anastasia; Antonakos, Nikolaos; Damoraki, Georgia; Gkavogianni, Theologia; Adami, Maria-Evangelia; Katsaounou, Paraskevi; Ntaganou, Maria; Kyriakopoulou, Magdalini; et al. (Cell host & microbe, 2020)
Proper management of COVID-19 mandates better understanding of disease pathogenesis. The sudden clinical deterioration 7–8 days after initial symptom onset suggests that severe respiratory failure (SRF) in COVID-19 is driven by a unique pattern of immune dysfunction. We studied immune responses of 54 COVID-19 patients, 28 of whom had SRF. All patients with SRF displayed either macrophage activation syndrome (MAS) or very low human leukocyte antigen D related (HLA-DR) expression accompanied by profound depletion of CD4 lymphocytes, CD19 lymphocytes, and natural killer (NK) cells. Tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) production by circulating monocytes was sustained, a pattern distinct from bacterial sepsis or influenza. SARS-CoV-2 patient plasma inhibited HLA-DR expression, and this was partially restored by the IL-6 blocker Tocilizumab; off-label Tocilizumab treatment of patients was accompanied by increase in circulating lymphocytes. Thus, the unique pattern of immune dysregulation in severe COVID-19 is characterized by IL-6-mediated low HLA-DR expression and lymphopenia, associated with sustained cytokine production and hyper-inflammation. [Display omitted] •Severe COVID-19 patients display immune dysregulation or macrophage activation syndrome•Severe respiratory failure is associated with a major decrease of HLA-DR on CD14 monocytes•CD4 cell and NK cell cytopenias are characteristics of severe COVID-19•IL-6 blocker Tocilizumab partially rescues SARS-CoV-2-associated immune dysregulation Proper management of COVID-19 mandates better understanding of disease pathogenesis. Giamarellos-Bourboulis et al. describe two main features preceding severe respiratory failure associated with COVID-19: the first is macrophage activation syndrome; the second is defective antigen-presentation driven by interleukin-6. An IL-6 blocker partially rescues immune dysregulation in vitro and in patients.